TREN URBANISASI DI INDONESIA - Felecia P. Adam (Puslit Kependudukan dan Pengembangan SDM Universitas Udayana, 2010)
Urbanization always give negative and positive influences to the development in anysectors. Impact that has been occurred from this process is not only be implicated to the aspect ofspacing, but also to social, economy, and cultural aspect. The consequences of urbanization flowrapidly to urban area will cause the slum settlements spread widely, and the micro informalsectors are mushrooming. Informal sector is really developed rapidly and profitable, but it has aconsequence to the increasing of poverty. This condition will disturb the urban structure becausebuffer area like “DAS” will be the target of settlement. The increasing of labor force which couldnot be involved in the industry are able to bring about internal conflict in the sector ofmanpower, like unemployment. Social and services facilities became increasingly as a reactionof user demand, however the benefit does not spread evenly because of high cost operating.The analysis of secondary data in this article/writing will try to show the urbanizationcondition in Indonesia and its developments.